Managing Newborn Screening Repeat Collections for Sick and Preterm Neonates - Ronda F. Greaves; Jo-Ann Northfield; Lauren Cross; Nazha Mawad; Thanh Nguyen; Maggie Tan; Michele A. O'Connell; James Pitt (MDPI AG, 2024)
Some preterm and sick neonates have altered biochemical profiles and follow-up newborn screening (NBS) collections are recommended. The Victorian NBS program historically recommended repeat collections for babies with birth weight < 1500 g (managed by the maternity service provider) and 3 weeks post-transfusion (managed by the laboratory). We aimed to determine adherence to current guidelines and review the guidelines to improve NBS performance. To do this, we audited data from 348,584 babies between January 2018 and June 2022. Babies with a recorded birth weight of <1500 g were filtered for inclusion. For the overall review and visualization of the protocol, we sourced information from the literature, our professional society and tertiary hospital services. A total of 2647 babies had a birth weight recorded between 200 and 1499 g. Of these, 2036 (77%) had a second sample collected, indicating that >1 in 5 babies were not receiving a follow-up collection. Our timing of repeat collections for transfused babies, requiring a 3-week follow-up collection, was longer than in other Australasian jurisdictions. A new combined "sick-prem protocol" was launched to support repeat collections and after a 1-year review achieved 95% compliance. We recommend NBS laboratories audit preterm and sick neonate repeat collections to ensure appropriate follow-up. This should be supported with a visual process map to aid education and compliance.